A taxonomic review of Korean Hydroglyphus Motschulsky (Coleoptera: Dytiscidae: Hydroporinae) with a description of new species. Issue 5 (1st June 2016) - Lee, Dae‐Hyun; Ahn, Kee‐Jeong
Abstract: A taxonomic study of Hydroglyphus Motschulsky in Korea is presented. Four species are recognized including a new species, Hydroglyphus coreanus sp. nov. Hydroglyphus flammulatus (Sharp) is reported for the first time in the Korean peninsula and H . geminus (Fabricius) is a new addition to the South Korean fauna. Habitus and SEM photographs, distribution maps, and key to the Korean species are provided.